Approaches for the establishment of optimized co-culture system of multiple Trichoderma strains for culture metabolites highly effective in cucumber growth promotion - Liu, Hongyi; Hao, Dazhi; Li, Yaqian; Wang, Xinhua; Chen, Jie (Frontiers in Microbiology, 2022)
In most cases, co-culture of Trichoderma and other microorganism principally takes advantage of biological control of plant diseases, which is superior to axenic culture. However, the approach to establish the optimal co-culture system of multiple Trichoderma strains was less studied, particularly for high production of microbial metabolites synergistically to promote plant growth and antagonistic activity against pathogens. The inoculation technique, fermentation kinetic modeling and response surface methodology were used to obtain the optimal inoculum sequence, fermentation time and co-culture nutrient formula. It was demonstrated that co-culture metabolites of Trichoderma strains obtained by simultaneous inoculation were more effective than those by sequence inoculation in promoting cucumber seedling growth. Furthermore, the optimal fermentation time was determined at 96-120 h by evaluating fermentation kinetic model, the activities of inhibitory potential of pathogenic Fusarium and cucumber seedling hypocotyl growth. Interestingly, the optimized nutrient formula was set to make co-culture metabolites of Trichoderma strains more effective in the plant growth promotion, which was determined through the assessment of cucumber test-tube plantlet. The components and each concentration in the optimized medium were confirmed at corn flour 16.22 g·L-1, potassium hydrogen phosphate 1.13 g·L-1, tryptophan 0.154 g·L-1, seaweed residue 30 g·L-1, ferrous sulfate heptahydrate 1 g·L-1 and ammonium sulfate 1.5 g·L-1. The hypocotyl length increased in the treatment with co-culture metabolites from the optimal medium by 2.3-fold compared with control. Thus, the results provide an optimal co-culture system of Trichoderma multiple strains aiming to produce high activity of metabolites in plant growth promotion.